Vanadocene complexes bearing N,N'-chelating ligands: Synthesis, structures and in vitro cytotoxic studies on the A549 lung adenocarcinoma cell line - Melounková, Lucie; Machálková, Aneta; Havelek, Radim; Honzíček, Jan; Řezáčová, Martina; Císařová, Ivana; Peterová, Eva; Vinklárek, Jaromír (Journal of inorganic biochemistry, 2019)
Ten new vanadocene complexes bearing N,N'-chelating ligands were prepared, characterized, and their cytotoxicity toward a panel of cancer cells was measured. Structures of four vanadocene compounds were determined by single crystal X-ray diffraction analysis. Complexes containing 1,2-bis(phenylimino)acenaphthene (bian) and 1,2-bis(4-methoxyphenylimino)acenaphthene (4-MeO-bian) exhibit higher cytotoxicity than those with dipyrido[3,2-a:2',3'-c]phenazine (dppz) and (E)-N-((pyridin-2-yl)methylene)benzenamine (pyma). In light of the finding, cytotoxic mechanisms of two highly effective complexes [(η5-C5H4Me)2V(bian)][OTf]2 (3b) and [(η5-C5H4Me)2V(4-MeO-bian)][OTf]2 (4b) against human A549 lung adenocarcinoma cells were investigated by following membrane leakage of intracellular lactate dehydrogenase, Trypan Blue staining and activation of tumor protein p53 (p53). Evaluated complexes have a potent dose-dependent antiproliferative activity, causing cell cycle redistribution by the increased accumulation of cells in the G2 and S phase. In accord with the observed cell cycle deceleration, cyclin-dependent kinase inhibitor-interacting protein 1 (p21WAF1/Cip1), extracellular signal-regulated kinases 1 and 2 (ERK1/2), Checkpoint kinase 1 (Chk1), Checkpoint kinase 2 (Chk2) and their phosphorylated forms Chk1 at serine 345 and Chk2 at threonine 68 increased. In the cells exposed to complexes, dose- and time-dependent apoptotic process is initiated by the activation of the initiator caspase 8, followed by activation of effector caspase 3/7 and phosphatidylserine externalization. Moreover, because of treatment, A549 cells activate prosurvival mitogen-activated protein kinases (MAPK) signaling and up-regulate antiapoptotic protein B-cell lymphoma (Bcl-2), thereby promoting evasion of cell death. Both complexes exhibited considerably higher cytotoxic effect than the reference anticancer drug cis-platin and the cytotoxicity was more pronounced at higher treatment time.
Keywords: Antineoplastic Agents; Vanadium; chelátory; apoptóza; Chelating Agents; kaspasy; Apoptosis; molekulární struktura; komplexní sloučeniny; Ligands; G2 Phase Cell Cycle Checkpoints; Caspases; screeningové testy protinádorových léčiv; lidé; Coordination Complexes; kontrolní body fáze G2 buněčného cyklu; nádorové buněčné linie; ligandy; Drug Screening Assays, Antitumor; Cell Proliferation; protinádorové látky; Humans; Cell Line, Tumor; proliferace buněk; Molecular Structure; vanad